2022
DOI: 10.32942/x2c88t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temperature change effects on marine fish range shifts: a meta-analysis of ecological and methodological predictors

Abstract: The current effects of global warming on marine ecosystems are predicted to increase, with species responding by changing their spatial distributions. Marine ectotherms such as fish experience elevated distribution shifts, as temperature plays a key role in physiological functions and delineating population ranges through thermal constraints. Distributional response predictions necessary for population management have been complicated by high heterogeneity in magnitude and direction of movements, which may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…In addition, there is much to be learnt by studying range shifts in a community context (Lavergne et al., 2010), including through the lens of invasion biology by exploring the role of biotic resistance based on key functional traits (e.g., Miller et al., 2023). Accounting for the effects of different methods used to assess range shifts and reducing research biases : The influence of the estimation process on range shift detection is increasingly recognized and would benefit from being explicitly accounted for when trying to make inference on the role of species traits in large cross‐taxa analyses (e.g., Brown et al., 2016; Dahms & Killen, 2023; Lenoir et al., 2020). This is especially true as the choice and effect of methodological factors may covary with species traits (e.g., when species detectability varies with life history or behavioral traits), ultimately decreasing our power to explain range shifts.…”
Section: A Path To Move Forwardmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is much to be learnt by studying range shifts in a community context (Lavergne et al., 2010), including through the lens of invasion biology by exploring the role of biotic resistance based on key functional traits (e.g., Miller et al., 2023). Accounting for the effects of different methods used to assess range shifts and reducing research biases : The influence of the estimation process on range shift detection is increasingly recognized and would benefit from being explicitly accounted for when trying to make inference on the role of species traits in large cross‐taxa analyses (e.g., Brown et al., 2016; Dahms & Killen, 2023; Lenoir et al., 2020). This is especially true as the choice and effect of methodological factors may covary with species traits (e.g., when species detectability varies with life history or behavioral traits), ultimately decreasing our power to explain range shifts.…”
Section: A Path To Move Forwardmentioning
confidence: 99%
“…The methods used to document range shifts influence the range shift estimates and our ability to detect meaningful relationships with species traits (Brown et al., 2016; Dahms & Killen, 2023; Lenoir et al., 2020). Similarly, research biases may not only result in an incomplete picture of which species and areas are vulnerable to climate change but also alter our comprehension of the underlying drivers of range shifts (Feeley et al., 2017; Lenoir et al., 2020).…”
Section: Assess the Effects Of The Estimation Process And Research Bi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Range shifts can cause changes to the structure of ecological communities as the influx of warmer water species into cooler climates results in altered species interactions and potential habitat change [5][6][7][8]. However, biodiversity monitoring programs in marine waters tend to be too small in temporal and spatial scale to make conclusions about species redistribution, requiring meta-analyses of multiple datasets to gather evidence from across many species, time periods and locations [9]. These analyses could be biased towards range extending species if studies from species and locations with few shifts observed are less frequently published.…”
mentioning
confidence: 99%